Factors affecting diabetes management among tuberculosis-diabetes comorbid patients in Udupi District - Ansuman Swain; Arathi P Rao; S V Chidananda Sanju; Saurabh Kumar (Wolters Kluwer Medknow Publications, 2021)
Background: Tuberculosis (TB)-diabetes comorbid cases have increased in India with Karnataka among the states with the highest numbers. The comorbidity adversely affects the prognosis of individual diseases. Diabetes management is crucial to the management of TB. Aim: This study aims to understand the factors influencing diabetes management, and the barriers and challenges affecting the management of diabetes in TB-Diabetes comorbid patients in Udupi district. Materials and Methods: For this mixed-method, cross-sectional study, TB-Diabetes comorbid patients, registered under the NIKSHAY in 2018 and 2019, and government Medical Officers were included in the study. Data were analyzed using SPSS. For the qualitative study, thematic analysis was done. Results: A total of 154 participants were included in the study. The disease the participant developed first, the place of diabetes diagnosis, person initiating diabetes treatment, and counseling (P < 0.05), were some of the factors affecting diabetes management. In addition, alcoholism, migrant status, and old age were some of the barriers in the management of diabetes among comorbid patients. Conclusion: Diabetes management of alcoholics, migrants, elderly patients, and patients without a family needs special consideration for the successful management of TB-Diabetes comorbidity.